The Vascular Microenvironment and Systemic Sclerosis. (23rd July 2010) - Frech, Tracy; Hatton, Nathan; Markewitz, Boaz; Scholand, Mary Beth; Cawthon, Richard; Patel, Amit; Sawitzke, Allen
Abstract : The role of the vascular microenvironment in the pathogenesis Systemic Sclerosis (SSc) is appreciated clinically as Raynaud's syndrome with capillary nail bed change. This manifestation of vasculopathy is used diagnostically in both limited and diffuse cutaneous subsets of SSc, and is thought to precede fibrosis. The degree of subsequent fibrosis may also be determined by the vascular microenvironment. This paper describes why the vascular microenvironment might determine the degree of end-organ damage that occurs in SSc, with a focus on vascular cell senescence, endothelial progenitor cells (EPC) including multipotential mesenchymal stem cells (MSC), pericytes, and angiogenic monocytes. An explanation of the role of EPC, pericytes, and angiogenic monocytes is important to an understanding of SSc pathogenesis. An evolving understanding of the vascular microenvironment in SSc may allow directed treatment.